THE DOCUMENTATION OF SELAYAH KERINGKAMEMBROIDERY PROCESS IN SARAWAK - Genevieve, Tsar Brennam; Adyatul, Julkree; Nor Szashashiqhin, Zainal Ibidin; Qistina Donna, Lee Abdullah (UNIMAS Publisher, 2021)
This study aims to investigate the process ofSelayah Keringkamembroidery in Sarawak as well as understanding the intricacy of art and expertisein producing the Selayah Keringkam embroidery that is now becoming thestatus of Malay women in Sarawak. This study was conducted to examineseveral types and processing stages of Selayah Keringkam, thus, to understand expertise inproducing Selayah Keringkam embroidery in more depth in order to maintain the uniqueness ofSelayah Keringkamart for the people of Sarawak. The study involved Malay women in Sarawak who have experiences in processing and stylingSelayah Keringkam. The information obtained inorder to meet the objectives of this study was taken from websites and journals that have beenpublished and studied further through researchmethodology and previous studies. Research datawere analyzed and displayed quantitatively and qualitatively. From the findings of this study, thereare various Selayah Keringkamembroideryprocesses that have been researched andrecorded in archives, journals and articles relatedto Selayah Keringkam.